Proceedings of the international conference on econutrition the nexux among human nutrition, ecology, agriculture, and economics - Bayna-Mariano, Recelyn I.; Gonzales, Pamela A.; Lalap, Belinda A.; Talavera, Ma. Theresa M.; Dela Vega, Anna Lorraine D. (2014)
The Institute of Human Nutrition and Food (IHNF) organized the 1st International Conference on Econutrition on July 4 to 5, 2013. The goals of the conference were to: (i) gather scientific information and experiences into an integrative body of knowledge in order to identify knowledge gaps and issues on econutrition; (ii) set directions for policy, research and development, academic programs, and capacity building on Econutrition; (iii) promote partnerships, linkages and collaborative work among different sectors involved in econutrition work; and (iv) craft a consensus on the adoption of econutrition as a strategy to ensure nutrition security in the country. The private sector, civil society, food and nutrition practitioners, economists, agriculturists, teachers, students, researchers, extension workers, community leaders, and scientists who attended the conference shared and disseminate state-of-the-art knowledge and experiences on econutrition and policies on econutrition and human health, agriculture and food production, environmental health, and economic development and other econutrition-related topics. This report presents the highlights of the lectures and discussions in the conference addressing econutrition from different angles and in deeper sense. The conference depicted the broad themes in econutrition and identified the issues and gaps in aid of setting the directions for policy, research and development, academic or curricular programs, and capacity building on econutrition. Harmonized efforts as having one national monitoring and evaluation framework with emphasis on achieving results are needed to address the challenges on econutrition.
Keywords: Econutrition; Health, Ecological; Nutrition